The Balance of Power in Household Decision-Making: Encouraging News on Gender in Southern Sulawesi - Colfer, C.J.P.; Achdiawan, R.; Roshetko, James M.; Mulyoutami, E.; Yuliani, L.; Mulyana, A.; Moeliono, M.; Adnan, H.; Erni (Elsevier, 2015)
Analyses of intra-household decision-making in Sulawesi are linked to gender issues shown to affect involvement in landscape management. These include agriculture, food, money, life chances, and attitudes toward domestic violence. The picture portrayed is encouraging, showing the social sophistication of a group often marginalized: This group shows considerable female involvement in decision-making and strongly democratic elements. We identify three issues that need greater attention—for equitable landscape management to result: women’s spheres of decision-making must be ascertained and taken into account, men’s involvement in care needs to expand, and women’s agency requires enhancement and external support.